Patterns of β-diversity and similarity reveal biotic homogenization of epiphytic lichen communities associated with the spread of black locust forests. (April 2015) - Nascimbene, Juri; Lazzaro, Lorenzo; Benesperi, Renato
Abstract: We compared epiphytic lichen communities of native broadleaved and secondary black locust ( Robinia pseudoacacia ) forests to detect possible differences in community structure that could be indicative of biological homogenization enhanced by the replacement of native by black locust forests. The study was carried out in two areas of Italy with different bioclimatic conditions using a balanced stratified random sampling. Results reveal a different pattern of community structure between native and black locust forests across the two regions that may reflect a process of biological homogenization. In particular, lichen communities of black locust forests share several species between the two study regions. This pattern of floristic homogenization parallels with a functional homogenization related to the spread of highly competitive species. This research provides early evidence that the decrease of native forests associated with the spread of black locust is a mechanism triggering biological homogenization of the epiphytic lichen biota. Highlights: Patterns of β-diversity components differ between native and black locust forests. The spread of black locust triggers biological homogenization of epiphytic lichens. The floristic homogenization parallels with a functional homogenization.